Histopathological characteristics of carcinoma of the uterine cervix in a tertiary hospital in southern Nigeria (2020)
Carcinoma of the uterine cervix is the fourth‑most common cancer among women worldwide, and the leading cause of cancer‑related death for women in developing countries. Objective: Cervical carcinoma is a major cause of mortality in a developing nation such as Nigeria. This study provides an update on the prevalence of pathological variants of cervical carcinomas seen at the University College Hospital, Ibadan, Southwestern Nigeria. Materials and Methods: This is a retrospective study involving the review of all the histologically diagnosed cervical carcinoma in the Department of Pathology, University College Hospital, Ibadan between January 2012 and December 2016. The histologically diagnosed cancers and the relevant clinical and histopathological information relating to these tumors were extracted from the records of the department. All cases were treated as anonymous with strict confidentiality. The cases were classified using the World Health Organization histological classification of tumors of the cervix (2014). The obtained data were analyzed using the Statistical Package for the Social Sciences version 23. Results: A total of 294 cases were included in this study. The peak age of diagnosis was in the 6th decade. Two hundred and fifty‑two cases (86.0%) were squamous cell carcinoma, 18 cases (6.1%) were adenocarcinomas, 16 cases (5.5%) were adenosquamous carcinomas, and 6 cases (2.2%) were adenoid cystic carcinomas, and one representing 0.3% was a neuroendocrine carcinoma. The most common histological grade was moderately differentiated (Grade 2). The large cell nonkeratinizing squamous cell carcinoma was the most common histological variant. Conclusion: A majority of cervical carcinomas are squamous cell carcinomas and are majorly the large cell nonkeratinizing variant.